Dent Oral Craniofac Res 2016
DOI: 10.15761/docr.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tongue movements on masticatory efficiency

Abstract: Introduction:The purpose of this study is to test relationships between tongue movements and electromyographic activity (EMA) of suprahyoid muscles. Methods:The subjects were 6 adults with a normal stomatognathic system. Experiment 1: Each subject performed six types of tongue movement: 1. extrusive, 2. right-and-left lateral, 3. upward, 4. downward, 5. touching the palate with the tongue tip, 6. touching the palatal aspects of the maxillary second molars, while EMAs were recorded with a wireless electrode-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the normal deglutition process, differences occur depending on the properties of the bolus; however, the tongue pressure and suprahyoid control tongue movements simultaneously from the early stage of the oral phase [31,32]. Taniguchi et al [33] measured suprahyoid muscle activity www.e-arm.org according to tongue position in normal subjects using surface EMG and confirmed that suprahyoid activity increased under tongue protrusion. Thus, tongue movement is closely related to suprahyoid muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal deglutition process, differences occur depending on the properties of the bolus; however, the tongue pressure and suprahyoid control tongue movements simultaneously from the early stage of the oral phase [31,32]. Taniguchi et al [33] measured suprahyoid muscle activity www.e-arm.org according to tongue position in normal subjects using surface EMG and confirmed that suprahyoid activity increased under tongue protrusion. Thus, tongue movement is closely related to suprahyoid muscle activity.…”
Section: Discussionmentioning
confidence: 99%